2014
DOI: 10.1089/neu.2013.3059
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Impaired Plasticity after Traumatic Brain Injury in the Developing Brain

Abstract: The robustness of plasticity mechanisms during brain development is essential for synaptic formation and has a beneficial outcome after sensory deprivation. However, the role of plasticity in recovery after acute brain injury in children has not been well defined. Traumatic brain injury (TBI) is the leading cause of death and disability among children, and long-term disability from pediatric TBI can be particularly devastating. We investigated the altered cortical plasticity 2-3 weeks after injury in a pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 59 publications
(77 reference statements)
5
31
0
Order By: Relevance
“…For example, while reduced axial diffusivity was reported to acutely follow CCI in the presence of axonal damage without myelin changes, a second study in the same model found that weeks after injury, when demyelination became evident, reduced anisotropy was no longer accompanied by reduced axial diffusivity but, instead, by increased radial diffusivity. This is supported by similar findings of increased radial diffusivity in a model with demyelination without axonal damage (Sun et al, 2006) as well as subsequent studies demonstrating DTI changes primarily in anisotropy with abnormal myelin staining (Budde et al, 2011;Jiang et al, 2011;Li et al, 2014). Notably, changes in myelination and myelinated fibers may influence anisotropy differently depending on the tissue investigated.…”
Section: Myelin Damage and Lossmentioning
confidence: 52%
See 2 more Smart Citations
“…For example, while reduced axial diffusivity was reported to acutely follow CCI in the presence of axonal damage without myelin changes, a second study in the same model found that weeks after injury, when demyelination became evident, reduced anisotropy was no longer accompanied by reduced axial diffusivity but, instead, by increased radial diffusivity. This is supported by similar findings of increased radial diffusivity in a model with demyelination without axonal damage (Sun et al, 2006) as well as subsequent studies demonstrating DTI changes primarily in anisotropy with abnormal myelin staining (Budde et al, 2011;Jiang et al, 2011;Li et al, 2014). Notably, changes in myelination and myelinated fibers may influence anisotropy differently depending on the tissue investigated.…”
Section: Myelin Damage and Lossmentioning
confidence: 52%
“…For instance, observations in a model of focal cortical ischemia (Pierpaoli et al, 1993) have demonstrated increased diffusivity in nonischemic brain regions with edema adjacent to regions of decreased diffusivity where ischemic damage was later confirmed by histology. The implication of this for TBI research is that acutely increased diffusivity may indicate brain regions that undergo edema without cellular disruption, and possibly these areas will not progress to degenerative outcomes, while regions with acutely decreased diffusivity are more likely to have metabolic or Sato et al, 2001;Chen et al, 2003;Coleman, 2005;Stoica & Faden, 2010Assaf et al, 1997Van Putten et al, 2005;Immonen et al, 2009;Laitinen et al, 2015 axonal injury axon morphology changes including beading and varicosities reduction in anisotropy and reduction in diffusion, especially in the axial direction Johnson et al, 2013Budde et al, 2009;Jiang et al, 2011;Li et al, 2011;Bennett et al, 2012; van de Looij et al, 2012 neural plasticity sprouting, arborization increased number of coherent processes and new collaterals increased anisotropy and/or changed orientation Bach-y-Rita, 2003;Yiu & He, 2006;Werner & Stevens, 2015;Meaney & Smith, 2015Kharatishvili et al, 2007Hutchinson et al, 2012;Sierra et al, 2015 Oligodendrocytes demyelination direct damage, chronic pathology degenerating or lost decreased anisotropy Armstrong et al, 2016Jiang et al, 2011Budde et al, 2011;Li et al, 2014;Mac Donald, Dikranian, Song, et al, 2007 myelination repair remyelination regenerating normalized anisotropy…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, loss of Gabrb3 gene signaling is associated with deficits in sensory processing [90]. Post-TBI changes in plasticity can also lead to sensory processing deficits [91]. The sensory processing deficits observed following TBI are statistically different compared to the normal range seen in noninjured children [92].…”
Section: Shared Biochemical Mechanismsmentioning
confidence: 99%
“…Histopathology including profound neuronal injury and neuroinflammation has been demonstrated in rodent models of bTBI (de Lanerolle et al, 2011;Abdul-Muneer et al, 2013). Furthermore, bTBI has been suggested to result in suppression of synaptic plasticity in rat hippocampus (Miyazaki et al, 1992;Li et al, 2013a). Moreover, common biochemical and molecular mechanisms of brain injury have been demonstrated in a variety of bTBI models (Goldstein et al, 2012;Kochanek et al, 2013;Sosa et al, 2013;Turner et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%